A database of water chemistry in eastern Siberian rivers - Shiqi Liu; Ping Wang; Qiwei Huang; Olga I. Gabysheva; Zehong Li; Jialing Zhang; Ekaterina S. Kazak; Yu Liu; Tcogto Zh. Bazarzhapov; Raisa N. Shpakova; Viktor A. Gabyshev; Sergey P. Pozdniakov; et al. (Scientific Data, 2022)
Measurement(s) water chemistry Technology Type(s) chromatography and spectrometry Sample Characteristic - Environment hydrochemistry Sample Characteristic - Location Eastern Siberia